Contribution of afferent feedback and descending drive to human hopping - Zuur, Abraham T (Blackwell Science Inc, 2010)
During hopping an early burst can be observed in the EMG from the soleus muscle starting about 45 ms after touch-down. It may be speculated that this early EMG burst is a stretch reflex response superimposed on activity from a supra-spinal origin. We hypothesised that if a stretch reflex indeed contributes to the early EMG burst, then advancing or delaying the touch-down without the subject's knowledge should similarly advance or delay the burst. This was indeed the case when touch-down was advanced or delayed by shifting the height of a programmable platform up or down between two hops and this resulted in a correspondent shift of the early EMG burst. Our second hypothesis was that the motor cortex contributes to the first EMG burst during hopping. If so, inhibition of the motor cortex would reduce the magnitude of the burst. By applying a low-intensity magnetic stimulus it was possible to inhibit the motor cortex and this resulted in a suppression of the early EMG burst. These results suggest that sensory feedback and descending drive from the motor cortex are integrated to drive the motor neuron pool during the early EMG burst in hopping. Thus, simple reflexes work in concert with higher order structures to produce this repetitive movement.